Die goldenen Siegelringe der Ägäischen Bronzezeit - Becker, Nadine (2018)
Due to their high material value and their meaningful iconography, Aegean signet rings have already attracted considerable attention in research. The focus was often on the analysis and interpretation of images, however, an overall consideration of this extremely complex archaeological genre and its diverse functions within the Minoan-Mycenaean administration and society was lacking so far. For the first time, not only preserved rings but also imprints of signet rings on sealings are systematically investigated in this work, which allows a new understanding of the material and its transformation during the Aegean Bronze Age.